Reconstructing the Sentencing Paradigm: From Normative Dimensions to Human Rights‑Based Implementation in Indonesia's New Criminal Code and Criminal Procedure Code - Diwan Jagad Raya Mohamad (SEAN Institute, 2026)
The enactment of Indonesia's new Criminal Code (Law No. 1 of 2023) marks a historic normative shift from the colonial‑era retributive paradigm toward a pluralistic sentencing framework that explicitly integrates rehabilitation, restorative justice, and human rights protection. However, this legislative achievement remains incomplete and largely aspirational unless accompanied by effective implementation. This research employs a normative legal method with statutory, conceptual, and comparative approaches to critically examine the gaps between the new Code's human rights‑based provisions and the entrenched realities of judicial practice. The analysis identifies three fundamental barriers: a deeply rooted punitive judicial culture that defaults to imprisonment even when alternative sanctions are legally available; severe institutional capacity deficits, including understaffed probation services and the absence of national databases for community‑based programs; and the lack of meaningful appellate accountability for proportionality and human rights compliance. Without comprehensive strategies judicial training on human rights‑based sentencing, the establishment of a Sentencing Commission to develop empirical guidelines, procedural reforms to strengthen the draft Criminal Procedure Code, and sustained investment in alternative sanctions the new KUHP risks becoming a dead letter. The conclusion affirms that normative reform alone is insufficient; genuine reconstruction requires operational machinery, cultural transformation, and unwavering political commitment to place human dignity at the center of every sentence imposed.